Pancreatic perfusion and arterial‐transit‐time quantification using pseudocontinuous arterial spin labeling at 3T. Issue 1 (5th September 2018) - Taso, Manuel; Guidon, Arnaud; Zhao, Li; Mortele, Koenraad J.; Alsop, David C.
Abstract : Purpose: To demonstrate the feasibility of noninvasively measuring pancreatic perfusion using pseudocontinuous arterial spin labeling (ASL) and to derive quantitative blood‐flow and transit‐time measurements in healthy volunteers. Methods: A pseudocontinuous ASL sequence with background suppression and a single‐slice single‐shot fast‐spin‐echo readout was acquired at 3 T in 10 subjects with a single standard postlabeling delay (PLD) of 1.5 s and in 4 additional subjects with 4 PLD from 0.7 to 2 s. An imaging synchronized breathing approach was used to minimize motion artifacts during the 3 min of acquisition. Scan‐rescan reproducibility was assessed in 3 volunteers with single‐delay ASL. Quantitative blood flow and arterial transit time (ATT) were derived and the impact of ATT correction was studied using either subject‐specific ATT in the second group or an average ATT derived from the group with multidelay ASL for subjects with single‐delay ASL. Results: Successful ASL acquisitions were performed in all volunteers. An average pancreatic blood flow of 201 ± 40 mL/100 g/min was measured in the single‐delay group using an assumed ATT of 750 ms Average ATT measured in the multidelay group was 1029 ± 89 ms Using the longer, measured ATT reduced the measured flow to 162 ± 12 and 168 ± 28 mL/100 g/min with subject‐specific or average ATT correction, respectively. ASL signal heterogeneities were observed at shorter PLD, potentially linked to its complex vascular supply and islet distribution. Conclusions: ASL enables reliable measurement of pancreatic perfusion in healthy volunteers. It presents a valuable alternative to contrast‐enhanced methods and may be useful for diagnosis and characterization of several inflammatory, metabolic, and neoplastic diseases affecting the pancreas.